Reconstitution of different signal peptides for enhanced thermostable alpha amylase secretion in Bacillus subtilis - Da, Nguyen Thi; Thoa, Nguyen Kim; Man, Tran Dinh (Vietnam Journal of Science and Technology, 2018)
Three signal peptides of alpha amylase genes of three isolated strains that were Bacillus licheniformis DA23, Bacillus subtilis D5-2, Bacillus cereus CN1-5 were successfully sequenced. Three predicted “Sec – type” signal peptides have a length varying from 27 (CN1-5) to 33 residues (D5-2). The secretion of alpha amylase of the recombination B. subtilis 168MPgrac strain (pHV33–PgracAmy3BT2) with 71.4U/ml was larger than that of 168MPamy with 53.2U/ml. Base on analyzed rerults of PAGE and zymogram about molecular weight, alpha amylases in both strains were the same size, nearly 58kDa. The extracellular amylase activity of signal peptide SsubtilisD5.2 in 168M was highest with 76.4±4.3 U/ml in four signal peptide targets.